Effects of nitrogen deposition on carbon allocation between wood and leaves in temperate forests. Issue 2 (11th November 2022) - Gao, Meixia; Zhu, Feifei; Hobbie, Erik A.; Zhu, Weixing; Li, Shanlong; Gurmesa, Geshere A.; Wang, Ang; Fang, Xiaoming; Zhu, Jiaojun; Gundersen, Per; Huang, Kai; Wu, Zhou; et al.
Abstract : Societal Impact Statement: Increasing atmospheric nitrogen (N) deposition represents a major global change factor, but its long‐term effect on tree growth and carbon (C) sequestration remains uncertain. Our manipulation experiment and meta‐analysis reveal that N deposition in temperate and boreal forests promoted tree growth and the allocation of more C into wood than into leaves in China and worldwide. Thus, N deposition may increase forest C sequestration through enhanced wood production and distribution of C into stable sinks. In the context of achieving "Carbon Neutrality, " understanding how N deposition affect long‐term forest C sinks will help us with mitigation strategies under climate change. Summary: Increased nitrogen (N) deposition is driving many temperate and boreal forests in the Northern Hemisphere towards N saturation. However, it is uncertain how long‐term N deposition affects tree growth and carbon (C) allocation in these forests. To investigate this, we treated temperate larch and mixed forests in northeastern China with N additions for 8 years. In addition, we collected data from 25 N‐addition experiments in temperate and boreal forests worldwide to reveal the overall effects of N on tree growth and C allocation. Nitrogen additions significantly promoted total biomass increment by 24% in both study forests, with on average additional 8 kg C per kg N gain into woody biomass over the study period. Nitrogen additions increased the ratio of woody biomass increment to foliage litterfall production in the larch forest (by 34%). Literature data analysis also revealed greater N promotion on wood (24%) over foliage (9%) production. However, the positive effect on foliage diminished over time. These results combined imply that N deposition may promote tree growth in temperate and boreal regions and drive proportionally more photosynthate allocation into wood than leaves, thus may enhance forest C sequestration in the long run. Abstract : Increasing atmospheric nitrogen (N) deposition represents a major global change factor, but its long‐term effect on tree growth and carbon (C) sequestration remain uncertain. Our manipulation experiment and meta‐analysis reveal that N deposition in temperate and boreal forests promoted tree growth and the allocation of more C into wood than into leaves in China and worldwide. Thus, N deposition may increase forest C sequestration through enhanced wood production and distribution of C into stable sinks. In the context of achieving "Carbon Neutrality", understanding how N deposition affect long‐term forest C sinks will help us with mitigation strategies under climate change.